Characteristics of low back pain among nurses at general hospital in Medan: A cross-sectional study - Ferdiansyah, Denny; Jesslyn, Yoshe (Lentera Perawat, 2025)
Background Low back pain (LBP) remains a major occupational health issue, particularly in developing countries like Indonesia, where nurses are frequently exposed to prolonged standing, heavy lifting, and poor ergonomic practices. These conditions contribute to decreased productivity and quality of life. Objective This study aimed to examine the characteristics of low back pain among nurses at Royal Prima General Hospital Medan and to assess the relationship between postural risk (REBA scores) and disability level (ODI scores). Methods A cross-sectional study was conducted in May 2025, involving 65 nurses selected using proportional stratified random sampling. Data were collected using a demographic questionnaire, the Rapid Entire Body Assessment (REBA) for postural analysis, and the Indonesian version of the Oswestry Disability Index (ODI) to measure disability. Data were analyzed using Spearman correlation and the Mann-Whitney U test. Results The mean REBA score was 5.48 ± 2.67, and the mean ODI score was 11.68 ± 13.42. A significant positive correlation was found between REBA and ODI scores (r = 0.267, p = 0.033), indicating a weak but significant association between poor posture and increased disability. Nurses working ≥8 hours per day had significantly higher ODI and REBA scores (p < 0.05). No significant differences were found based on gender, work unit, or length of employment. Conclusion Prolonged working hours are associated with increased postural risk and disability levels among nurses. A weak but significant correlation exists between postural risk and low back disability. Early ergonomic interventions and better shift duration management are recommended to reduce the incidence of LBP. To our knowledge, this is one of the first studies in Indonesia utilizing both REBA and ODI among hospital nurses, contributing valuable local evidence to inform occupational health strategies